Role of Corporate Governance Application in Practice of Creative Accounting Methods-Applied Study on Listed Companies in Khartoum Exchange - Sayed A. Bala (Arab Economic and Business Journal, 2013)
The purpose of the research is the definition of Corporate Governance and its principles, importance, objectives, and knowledge of its role in reducing the practice of Creative Accounting, as well as its role in raising the efficiency of companies’ performance and Quality of Accounting Information. In this regard, the researcher used a descriptive analytical approach and looked into the theoretical and field relevant studies of Arabs and foreigners with the induction and presentation of the most important results, and the development of what supports the development of Corporate Governance and it is use in raising the efficiency of companies’ performance, and reducing the practice of Creative Accounting, with a field Study on Listed Companies in Khartoum Stock Exchange. The research came up with several conclusions, such as the influential role of Corporate Governance in raising the efficiency of its financial and administrative performance. Besides, Corporate Governance has an effective role in determining the Quality of Accounting Information and reducing the practice of Creative Accounting.